2020
DOI: 10.1186/s13059-020-02191-0
|View full text |Cite
|
Sign up to set email alerts
|

Potentially adaptive SARS-CoV-2 mutations discovered with novel spatiotemporal and explainable AI models

Abstract: Background A mechanistic understanding of the spread of SARS-CoV-2 and diligent tracking of ongoing mutagenesis are of key importance to plan robust strategies for confining its transmission. Large numbers of available sequences and their dates of transmission provide an unprecedented opportunity to analyze evolutionary adaptation in novel ways. Addition of high-resolution structural information can reveal the functional basis of these processes at the molecular level. Integrated systems biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(82 citation statements)
references
References 113 publications
4
76
0
Order By: Relevance
“…Our full genome analysis revealed that the wave 4 virus has several nonsilent mutations associated with host adaptation ( 4 6 ; B. Zhou et al, unpub. data, https://doi.org/10.1101/2020.10.27.357558 ), including mutations in the RNA-dependent RNA polymerase (RdRp[L323P]), Spike(D614G), open reading frame 3a (ORF3a[Q57H]), ORF3b(E14*), and nucleocapsid (N[S194L]) proteins.…”
Section: The Studymentioning
confidence: 99%
“…Our full genome analysis revealed that the wave 4 virus has several nonsilent mutations associated with host adaptation ( 4 6 ; B. Zhou et al, unpub. data, https://doi.org/10.1101/2020.10.27.357558 ), including mutations in the RNA-dependent RNA polymerase (RdRp[L323P]), Spike(D614G), open reading frame 3a (ORF3a[Q57H]), ORF3b(E14*), and nucleocapsid (N[S194L]) proteins.…”
Section: The Studymentioning
confidence: 99%
“…Nsp13 contains a helicase domain, allowing efficient strand separation of extended regions of double-stranded RNA and DNA (48). Dual mutations in Nsp13 were reported with profound effect on its activity specifically in Pacific northwest of USA (49). P409L, mutation leads to increased affinity of helicase RNA interaction, whereas Y446C is a destabilizing mutation increasing the molecular flexibility and leading to decreased affinity of helicase binding with RNA (50).…”
Section: Resultsmentioning
confidence: 99%
“…The coexistence of D614G (spike), P323L (NSP12), and C241U (5′-UTR) may contribute to increased transmission fitness [ 61 ]. The P323L variant might alter the secondary and tertiary structures of NSP12 to interact with NSP8, thereby affecting viral replication [ 62 , 63 ]. Additionally, other variants like S25L in NSP7, S194L, R203K, G204R, and T205I in nucleocapsid, T85I and I120F in NSP2, S477N in spike, and Q57H in ORF3a have also been confirmed by previous studies [ 62 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The P323L variant might alter the secondary and tertiary structures of NSP12 to interact with NSP8, thereby affecting viral replication [ 62 , 63 ]. Additionally, other variants like S25L in NSP7, S194L, R203K, G204R, and T205I in nucleocapsid, T85I and I120F in NSP2, S477N in spike, and Q57H in ORF3a have also been confirmed by previous studies [ 62 , 64 ]. Although many SARS-CoV-2 variants have been observed, their associations with viral loads and infectivity need more investigation.…”
Section: Discussionmentioning
confidence: 99%